(untitled) (Journal of Foreign Language Studies, 2024)
The boundary does not merely refer to nouns indicating things. The process of expressing behaviors through verbs has both beginning and end points, thus, can be considered a boundary. The article, based on the formation of boundary of nouns indicating things, discusses issues relating to the boundary of Chinese stative verbs. It then provides a classification of boundary of 373 stative verbs in “Modern Chinese Verbs Dictionary”.